2018
DOI: 10.1021/acs.jpcb.8b02303
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cation Effects on SCN in Bulk Solution and at the Air–Water Interface

Abstract: The large and sparsely hydrated thiocyanate anion, SCN, plays a prominent role in the study of specific ion effects in biological, colloid, and atmospheric chemistry due to its extreme position in the Hofmeister series. Using atomistic modeling of aqueous SCN solutions, we provide novel insight at the molecular scale into the experimentally observed differences in ion pairing, clustering, reorientation dynamics, mutual diffusion, and solubility between the sodium, Na, and the potassium, K, salt. Compared to KS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 74 publications
4
39
0
Order By: Relevance
“…3,4,51,[56][57][58][59] Specific ion effects are also observed (in this work and others), where small cations like Na + decrease d (and increase interfacial tension) more strongly than larger ions like Cs + 60,61. Although these observations are well-known for electrolyte/vapor and interfaces with non-polar solvents, the outcome in the presence of a polar immiscible solvent is not well studied.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…3,4,51,[56][57][58][59] Specific ion effects are also observed (in this work and others), where small cations like Na + decrease d (and increase interfacial tension) more strongly than larger ions like Cs + 60,61. Although these observations are well-known for electrolyte/vapor and interfaces with non-polar solvents, the outcome in the presence of a polar immiscible solvent is not well studied.…”
supporting
confidence: 63%
“…This sections first builds upon prior work that has investigated macroscopic ion induced perturbations to both the vapor and octanol interfaces. 60,[67][68][69] As observed when comparing water/vapor and water/octanol interfaces, within the electrolyte interfaces there exist significant differences in the relationship between γ, d, and ∆A in the presence of octanol. While trolyte containing interfaces, there is an increase to interfacial tension, as anticipated, in the vapor and octanol systems (Table 1).…”
Section: Ion Induced Perturbations To the Instantaneous Surface And Subjacent Layersmentioning
confidence: 92%
“…This is consistent with molecular dynamics simulations by Tesei et al at high concentrations (5 mol kg -1 ) which showed cations (Na + , K + ) to have negligible influence on the interfacial properties of thiocyanate at the air/water interface, even though the bulk properties showed significant differences. 16 In ESHG experiments at the dodecanol/water interface in our group, sodium and potassium thiocyanate salts (0-3 M) exhibited similar Gibbs free energies of adsorption, within experimental error, suggesting that cation effects at the interface for thiocyanate are minimal. 7 On the other hand, Venkateshwaran et al predicted the occurrence of "water-bridged" configurations at high ion concentrations, wherein a few hydration water molecules are shared by like-charged ions at and near the interface.…”
mentioning
confidence: 67%
“…14,15 A recent molecular dynamics study predicted that the sulfur has a greater affinity for the interface than does nitrogen, yielding an average tilt angle of 45°in the outermost surface layer. 16 Here, we probe the CTTS spectrum, which comprise broad, intense, and typically featureless bands in the deep UV (<250 nm), engendering the transfer of an electron from the anion to its surrounding solvent molecules. 17 Because the initial ground state of the anion and the excited CTTS states are defined by both the ion and its corresponding neutral species, as well as the surrounding solvent molecules, CTTS spectra are highly sensitive to the details of the chemical environment, making them powerful tools for elucidating complex chemical interfaces.…”
mentioning
confidence: 99%
“…A practical approach to deal with finite-size effects was proposed by Krüger and co-workers [35,37] where an expression for KB integrals for finite volumes was derived. The method of Krüger and co-workers [34,35,37,38] has been used in many studies [6,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. According to Hill's thermodynamics of small systems [56,57] (also called nanothermodynamics), KB integrals for finite volumes scale with the inverse of the characteristic length scale of the small system and this scaling can be extrapolated to the thermodynamic limit (i.e to KB integrals as defined by Kirkwood and Buff).…”
Section: Introductionmentioning
confidence: 99%